ARCS Model-Based Educational Game for Athletics in Physical Education - Steven Roseily; Ketut Agustini; Ni Nyoman Parwati (Jurnal Media dan Teknologi Pendidikan, 2025)
Physical Education, Sports, and Health (PJOK) learning, particularly in athletics, is often perceived as tedious and repetitive by students, leading to low learning motivation. This study aims to develop an educational game named "FitMove" based on the ARCS model (Attention, Relevance, Confidence, Satisfaction) and to test its validity, practicality, and effectiveness in increasing the learning motivation of junior high school students. This research is a Research and Development (R&D) study using the ADDIE model. The research subjects included material experts, media experts, practitioner teachers, and seventh-grade students at a Junior High School in Denpasar. Data collection utilized validation sheets, response questionnaires, and the Instructional Materials Motivation Survey (IMMS). The data were analyzed using descriptive quantitative analysis for validity and practicality, and a Paired Sample t-Test for effectiveness. The results showed that FitMove was declared very valid (I−CVI=1.00) and very practical by teachers (94.6%) and students (91.1%). The effectiveness test showed a significant increase in student learning motivation (p<0.001) with a post-test average score (144.00) higher than the pre-test (119.71). This research implies that integrating sensor-based gamification can effectively bridge the gap between digital play and physical exertion, offering a scalable solution for modernizing physical education.